If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 = 12z + 18 + -5 Reorder the terms: 7 = 18 + -5 + 12z Combine like terms: 18 + -5 = 13 7 = 13 + 12z Solving 7 = 13 + 12z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12z' to each side of the equation. 7 + -12z = 13 + 12z + -12z Combine like terms: 12z + -12z = 0 7 + -12z = 13 + 0 7 + -12z = 13 Add '-7' to each side of the equation. 7 + -7 + -12z = 13 + -7 Combine like terms: 7 + -7 = 0 0 + -12z = 13 + -7 -12z = 13 + -7 Combine like terms: 13 + -7 = 6 -12z = 6 Divide each side by '-12'. z = -0.5 Simplifying z = -0.5
| Y=yz+10 | | -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 | | 4z=2.5+2.7 | | 27=0.5x(2+7) | | 9-1/2b=5+8/2b | | xx=42 | | 4k^2-13k+3=0 | | 8-(4y-9)=5-5y | | -3x+22/2= | | (x-1/2)=(2-x/3) | | 5.4/-4.5y | | -10?4(3p?10)=18 | | -3x+9+3x=4 | | .2(5+2x)=4(.3x+.9) |